A Survey on the Effects of Gold-Nanoparticles in Allergic Asthma - Mehrabi Nasab, Didar; Taheri, Alireza; Jafari, Bahman; Athari, Seyyed Shamsadin (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Asthma is an inflammatory airway disease and allergies are the most important cause of asthma. Different types of drugs have been developed to control asthma, and the use of carrier systems to transfer drugs to the airways is an effective method. Gold nanoparticles (AuNP) is a subject of substantial research that can be easily synthesized and, in this study, the effect of gold nanoparticles on allergic asthma was evaluated. Methods: There are 4 groups of mice, including: the control group, the control group receiving AuNPs, the asthmatic group, and the asthmatic group receiving AuNPs. An animal model of asthma was produced using ovalbumin (OVA). The negative control group was sensitized and challenged with PBS. Broncho-alveolar lavage fluid (BALF) and lung tissue were collected, then quantitative real-time PCR for the four target genes (IL-4, IL-5, IL-13, and MUC5ac) and histopathological study of lung tissue was done. Results: In the OVA group, the mRNA expression of targeted genes had no significant differences (P>0.05). Mucus hypersecretion, goblet cell hyperplasia, peribronchial and perivascular inflammation had no significant difference between AuNPs receiving groups with non-treated groups (P>0.05). Conclusion: In this study, it was observed that AuNP did not affect asthma and control mice. These nanoparticles did not elicit any immune or allergic responses and can be easily used for therapeutic or diagnostic purposes. *Corresponding Authors: Alireza Taheri; Email: taheri@ilam-iau.ac.ir; Seyyed Shamsadin Athari, Email: ss.athari@zums.ac.ir Please cite this article as: Mehrabi Nasab D, Taheri A, Jafari B, Athari SS. A Survey on the Effects of Gold-Nanoparticles in Allergic Asthma. Arch Med Lab Sci. 2021;7:1-5 (e21). https://doi.org/10.22037/amls.v6.32761